2018
DOI: 10.1186/s12974-018-1066-z
|View full text |Cite|
|
Sign up to set email alerts
|

The role of the complement system in traumatic brain injury: a review

Abstract: Traumatic brain injury (TBI) is an important cause of disability and mortality in the western world. While the initial injury sustained results in damage, it is the subsequent secondary cascade that is thought to be the significant determinant of subsequent outcomes. The changes associated with the secondary injury do not become irreversible until some time after the start of the cascade. This may present a window of opportunity for therapeutic interventions aiming to improve outcomes subsequent to TBI. A prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 127 publications
3
117
0
Order By: Relevance
“…Under pathological conditions, excessive hippocampal C3 deposition has been implicated in the development of many neurological disorders [13, 14]. In the current model, we found an early and significant elevation of hippocampal C3 levels after orthopedic surgery, supporting the involvement of complement activation in the pathophysiology of PND.…”
Section: Discussionsupporting
confidence: 76%
“…Under pathological conditions, excessive hippocampal C3 deposition has been implicated in the development of many neurological disorders [13, 14]. In the current model, we found an early and significant elevation of hippocampal C3 levels after orthopedic surgery, supporting the involvement of complement activation in the pathophysiology of PND.…”
Section: Discussionsupporting
confidence: 76%
“…We chose to test the importance of one specific inflammatory pathway, the classical complement pathway, using a pharmacological tool to block C1q in TBI mice. C1q has a well-documented role in normal brain function such as synaptic pruning during development (24), as well as its 405 involvement in several neurological diseases (16)(17)(18)(19)(20)(21)(22). In addition, we had observed that C1q expression was highly increased in the corticothalamic circuit for up to four months after TBI ( Figure S2).…”
Section: C1q: Good or Bad? A Question Of Timingmentioning
confidence: 88%
“…The complement system is part of the innate immune response [59,60] and consists of serine proteases that are encoded from the same ancestral genes as coagulation proteins [61]. It functions as a form of intravascular surveillance that, when activated, amplifies and forms the complement cascade.…”
Section: The Complement Systemmentioning
confidence: 99%